Understanding care when cure is not likely for young adults who face cancer: a realist analysis of data from patients, families and healthcare professionals - Kenten, C; Ngwenya, N; Gibson, F; Flatley, M; Jones, L; Pearce, S; Wong, G; Black, K; Haig, S; Hough, R; Hurlow, A; Stirling, L; et al. (BMJ Publishing Group, 2019)
Objectives To understand the experiences of young adults with cancer for whom cure is not likely, in particular what may be specific for people aged 16–40 years and how this might affect care. Design We used data from multiple sources (semi-structured interviews with people with cancer, nominated family members and healthcare professionals, and workshops) informed by a preliminary programme theory: realist analysis of data within these themes enabled revision of our theory. A realist logic of analysis explored contexts and mechanisms affecting outcomes of care. Setting Three cancer centres and associated palliative care services across England. Participants We aimed for a purposive sample of 45 people with cancer from two groups: those aged 16–24 years for whom there may be specialist cancer centres and those 16–40 years cared for through general adult services; each could nominate for interview one family member and one healthcare professional. We interviewed three people aged 16–24 years and 30 people 25–40 years diagnosed with cancer (carcinomas; blood cancers; sarcoma; central nervous system tumours) with a clinician-estimated prognosis of <12 months along with nominated family carers and healthcare professionals. 19 bereaved family members and 47 healthcare professionals participated in workshops. Results Data were available from 69 interviews (33 people with cancer, 14 family carers, 22 healthcare professionals) and six workshops. Qualitative analysis revealed seven key themes: loss of control; maintenance of normal life; continuity of care; support for professionals; support for families; importance of language chosen by professionals; and financial concerns. Conclusions Current care towards end of life for young adults with cancer and their families does not meet needs and expectations. We identified challenges specific to those aged 16–40 years. The burden that care delivery imposes on healthcare professionals must be recognised. These findings can inform recommendations for measures to be incorporated into services.